Research of the Influence of Tooth Surface Wear and Bearing Clearance on Gear Dynamics - Kaida Wang; Ruiliang Zhang; Tie Wang; Yatian Zhou; Fei Wang (Jixie chuandong)
Tooth surface wear and bearing clearance are important factors affecting gear system dynamics, in order to reveal the influence of tooth wears and bearing clearance on the dynamics of gear system, a six-degree-of-freedom bending-torsion coupled model is established, which takes into account the tooth surface wear, bearing clearance, friction and backlash. The dynamic differential equations are solved by Runge-Kutta method and the dynamic response of the system is obtained. The results show that when the gear changes in unworn phase to mild wear phase, the amplitude of dynamic transfer error decreases and the vibration is weakened. With the increment of tooth surface wear, the amplitude of dynamic transmission error increases and the vibration is strengthened when the gear reaches severe wear phase. With the increase of bearing clearance, the peak-to-peak value of dynamic transfer error will increase and resonance phenomenon will appear, the stability of system will decrease.